Androgen Receptor Expression in ER and PR Negative Breast Cancer—A Study from a Tertiary Hospital in Northern India - Sidhu, Sumeet; Kwatra, Kanwardeep Singh; Kinsley, Pamela Alice (South Asian Journal of Cancer, 2023)
Objectives Breast cancer is the leading cause of cancer-related deaths in women. Estrogen (ER) and progesterone receptor (PR) status and Her2 overexpression are major determinants in therapeutic decision making. Triple-negative breast cancers (TNBCs) have limited treatment options. Androgen receptor (AR) expression opens up therapeutic avenues for these patients. The aim of this article was to study the immunohistochemical expression of ARs in ER and PR Negative breast carcinomas and to correlate AR expression with various clinical, histopathological, and other immunohistochemical parameters.Materials and Methods It is a cross-sectional study including 105 ER and PR Negative cases of breast carcinoma. Clinical parameters, histopathology, and immunohistochemical expression of AR, Her2, and Ki67 were analyzed in all cases.Results AR expression was observed in 63.8% of ER and PR Negative breast cancers. In this group, AR expression was strongly associated with Her2 co-expression (89.2%) as compared to TNBCs (45.8%); p-value = 0.0002. Significant correlation was also observed between AR expression and tumor necrosis (p-value = 0.034) and postmenopausal status (p = 0.007).Conclusion Our study shows that significant proportion of ER and PR Negative breast carcinomas (ER- PR- Her2+ and TNBCs) show AR expression. We strongly recommend routine evaluation of all hormone receptor-negative breast carcinomas for AR status by immunohistochemistry.
Keywords: androgen; breast carcinoma; estrogen; Her2; TNBC